2012
DOI: 10.1371/journal.pone.0037614
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Existing Diseases of Patients Increase Susceptibility to Hypoxemia during Gastrointestinal Endoscopy

Abstract: Hypoxemia is the most common adverse event that happened during gastrointestinal endoscopy. To estimate risk of hypoxemia prior to endoscopy, American Society of Anesthesiology (ASA) classification scores were used as a major predictive factor. But the accuracy of ASA scores for predicting hypoxemia incidence was doubted here, considering that the classification system ignores much information about general health status and fitness of patient that may contribute to hypoxemia. In this retrospective review of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 22 publications
1
24
1
Order By: Relevance
“… 21 23 However, other articles reported on other risk factors, such as diabetes, which were not significant factors in this study. 24 …”
Section: Discussionmentioning
confidence: 99%
“… 21 23 However, other articles reported on other risk factors, such as diabetes, which were not significant factors in this study. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Multivariable logistic regressions revealed that independent risk factors for hypoxemia include high body mass index, hypertension, diabetes, gastrointestinal diseases, heart diseases and procedures that combined esophagogastroduodenoscopy (EGD) and colonoscopy [32] . Hypoxemia occurs typically within 5 min of medication administration or endoscope intubation and only one third of all apnea and abnormal ventilation events eventually lead to hypoxemia [31] .…”
Section: Respiratory Depressionmentioning
confidence: 99%
“…In fact, we used it to measure the incidence of respiratory suppression in patients undergoing ESD and to assess the risk factors for respiratory suppression in these patients. Previous studies have shown that the incidence of respiratory suppression in patients undergoing gastrointestinal endoscopic treatment under conscious sedation ranges from 10 to 70%, depending on the definition of respiratory suppression, patient population, type of endoscopy, and type of sedatives [ 9 , 10 ]. Markedly, in these studies, pulse oximetrywas used as a surrogate measure of ventilation.…”
Section: Discussionmentioning
confidence: 99%